2021
DOI: 10.1093/neuonc/noab252
|View full text |Cite
|
Sign up to set email alerts
|

EANO, SNO and Euracan consensus review on the current management and future development of intracranial germ cell tumors in adolescents and young adults

Abstract: The incidence of intracranial germ cell tumors (iGCT) is much lower in European and North American (E&NA) than in Asian population. However, E&NA cooperative groups have simultaneously developed with success treatment strategies with specific attention paid to long-term sequelae. Neurological sequelae may be reduced by establishing a diagnosis with an endoscopic biopsy and/or cerebrospinal fluid (CSF) and/or serum analysis, deferring the need to perform a radical surgery. Depending on markers and/or hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 80 publications
1
109
1
Order By: Relevance
“…Tumor markers (human chorionic gonadotropin (HCG) and alpha fetoprotein (AFP)) in serum and cerebrospinal fluid (CSF) are useful for diagnosis [ 8 ], the evaluation of treatment response [ 9 ], and detecting recurrence after treatment [ 10 ]. GCTs have been shown to transform histologically following treatment, with associated fluctuations in tumor markers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor markers (human chorionic gonadotropin (HCG) and alpha fetoprotein (AFP)) in serum and cerebrospinal fluid (CSF) are useful for diagnosis [ 8 ], the evaluation of treatment response [ 9 ], and detecting recurrence after treatment [ 10 ]. GCTs have been shown to transform histologically following treatment, with associated fluctuations in tumor markers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, classifications differ in Europe, North America, and Japan. In Europe/North America, NGGCT is defined according to a case presentation in which tumor markers are elevated or according to histopathological confirmation of NGGCTs when tumor markers are normal ( 10 ). In Japan, NGGCT is further subdivided into two classes: an intermediate prognosis group and a poor prognosis group ( 3 , 11 )., The intermediate prognosis group includes immature teratomas, teratomas with somatic-type malignancy, and mixed tumors (mainly composed of germinomas and teratomas).…”
Section: Non-germinomatous Germ Cell Tumorsmentioning
confidence: 99%
“…Tumor markers (HCG and AFP) are examined in blood serum and cerebrospinal fluid (CSF) from lumbar puncture or ventricular drainage when it is safe to obtain the sample for the latter. If tumor markers are elevated, patients are diagnosed with NGGCTs; if not, patients require a biopsy for histopathological diagnosis (6)(7)(8)(9)(10). In Japan, treatment stratification is unique in that it is based on three prognostic subgroups (i.e., germinoma, intermediate prognosis, and poor prognosis subgroups) that are determined according to histopathological confirmation (Table 1) (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Within this statistic there are significant variations between European countries. Clinical trials have shown remarkable advances, such as intra-cranial germ cell tumors ( 5 ) and medulloblastoma ( 6 ), which have improved with combined standard approaches of well delivered chemotherapy, radiotherapy and rational approaches to surgery. Radiotherapy research and trials in the past decades have focussed upon optimising radiation doses to the tumour and surrounding brain to minimise the cognitive consequences ( 7 ).…”
Section: Context Of Research In Childhood Brain Tumorsmentioning
confidence: 99%